Bis(dimethylmalonato-κ(2) O,O′)bis[4-(4-pyridylamino-κN (4))pyridinium]nickel(II) hexahydrate - Farnum, Gregory A. (International Union of Crystallography, 2008)
In the title compound, [Ni(C(5)H(6)O(4))(2)(C(10)H(10)N(3))(2)]·6H(2)O, divalent nickel ions situated on the crystallographic twofold axis are octahedrally coordinated by four O atoms from two dimethylmalonate ligands in a 1,3-chelating mode and two N atoms from two protonated monodentate 4,4′-dipyridylamine molecules. The molecules link into chains via N—H⋯O hydrogen bonding mediated by protonated pyridyl groups. The chains form layer patterns via π–π stacking [centroid–centroid distance = 3.777 (2) Å] . Water molecule hexamers are generated from the unligated water molecules (three per asymmetric unit) by inversion centers at Wyckoff position d. These clusters are situated between the pseudolayers, providing hydrogen-bonding pathways that build up the three-dimensional structure.